2015
DOI: 10.1371/journal.pone.0144385
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cardiac Diseases during Pregnancy on Severe Maternal Morbidity and Mortality in Brazil

Abstract: BackgroundTo evaluate maternal heart disease as a cause or complicating factor for severe morbidity in the setting of the Brazilian Network for Surveillance of Severe Maternal Morbidity.Methods and FindingsSecondary data analysis of this multicenter cross-sectional study was implemented in 27 referral obstetric units in Brazil. From July 2009 to June 2010, a prospective surveillance was conducted among all delivery hospitalizations to identify cases of severe maternal morbidity (SMM), including Potentially Lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
0
16
0
7
Order By: Relevance
“…They were organized in two research groups. The first refers to two articles from the "Nascer no Brasil" ("Born in Brazil") study, 5,34 the second reports 13 articles from the Multicenter Study of the "Rede Nacional de Vigilância de Morbidade Materna Grave" [35][36][37][38][39][40][41][42][43][44][45][46][47] ('National Surveillance Network on Severe Maternal Morbidity"). All articles of national scope used the WHO criteria for near miss.…”
Section: National Hospital Based Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They were organized in two research groups. The first refers to two articles from the "Nascer no Brasil" ("Born in Brazil") study, 5,34 the second reports 13 articles from the Multicenter Study of the "Rede Nacional de Vigilância de Morbidade Materna Grave" [35][36][37][38][39][40][41][42][43][44][45][46][47] ('National Surveillance Network on Severe Maternal Morbidity"). All articles of national scope used the WHO criteria for near miss.…”
Section: National Hospital Based Studiesmentioning
confidence: 99%
“…Cecatti et al 35 present overall results, and the other articles explore MNM according to age group 36 and with specific conditions: abortion, 37 ectopic pregnancy, 38 hypertensive diseases, 39,40 hemorrhage, 41,42 infections, 43,44 heart diseases. 45 Healthcare factors were also analyzed, such as quality of care 46 and the association with cesarean section 47 based on Robson's Classification.…”
Section: National Hospital Based Studiesmentioning
confidence: 99%
“…In parallel, when assessing the impact of the heart disease during pregnancy, it was found that most complications that increase the maternal morbidity and mortality occur in women known to be heart disease bearers, reinforcing the importance of the Reproductive Planning. [3][4] Reproductive Planning is often confused with Family Planning and Preconception counseling. The later are tools that make up the former, which should start at the beginning of the sexual life, especially for women with heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 Heart disease has been pointed as the main cause of indirect obstetric maternal death worldwide and, in Brazil, also associated with increased near miss events. [2][3] The medical diagnosis of heart disease occurs previously the pregnancy classified as high risk due to the increased chance of maternal and fetal complications. The presence of predictors such as cyanosis, functional class greater than II, ventricular ejection fraction less than 40% and previous cardiovascular disorders, increase the additional risk of heart events in the gestational period by 25% and 75% this same risk if identified two or more factors.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal nearmiss occurred in 15% of cardiac patients compared to 7.7% in non-cardiac patients (p<0.001). Maternal death occurred in 4.8% and 1.2% of cardiac and non-cardiac patients respectively [11,12]. Finally, the link between hypertensive complications or preterm delivery and the risk of long term cardiovascular events or death have been recently highlighted [11].…”
Section: Page 4 Of 25mentioning
confidence: 99%